2015
DOI: 10.1371/journal.pone.0141763
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PIK3CA Mutations and Activation Pathways in Triple Negative Breast Cancer

Abstract: BackgroundTriple Negative Breast Cancer (TNBC) accounts for 12–24% of all breast carcinomas, and shows worse prognosis compared to other breast cancer subtypes. Molecular studies demonstrated that TNBCs are a heterogeneous group of tumors with different clinical and pathologic features, prognosis, genetic-molecular alterations and treatment responsivity. The PI3K/AKT is a major pathway involved in the regulation of cell survival and proliferation, and is the most frequently altered pathway in breast cancer, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 61 publications
2
56
1
Order By: Relevance
“…PIK3CA mutations are very frequent (20%-40%) genetic alterations in MBC, particularly in node-negative, ER þ and HER2 À breast cancer, and are generally related to a good clinical outcome with a lower recurrence and mortality rate (35). Nevertheless, tissue-based NGS had already demonstrated that at least 33% of TN breast cancer have deregulated PI3K/AKT pathways, making these pathways an attractive target for pharmacologic treatment (e.g., everolimus) and highlighting the importance of mutation profiling for individualized therapies (36). In our population, maybe because enriched in IBC (64% of the patients), with a rate of 40% in the entire population and of 31% in the TN subgroup, PIK3CA/mTOR pathway (altered in 22 patients, including 12 patients with IBC) appears the second most altered pathway, immediately after TP53 (52% and 61%, in the entire population and TN subgroup respectively).…”
Section: Secondary Objectivesmentioning
confidence: 99%
“…PIK3CA mutations are very frequent (20%-40%) genetic alterations in MBC, particularly in node-negative, ER þ and HER2 À breast cancer, and are generally related to a good clinical outcome with a lower recurrence and mortality rate (35). Nevertheless, tissue-based NGS had already demonstrated that at least 33% of TN breast cancer have deregulated PI3K/AKT pathways, making these pathways an attractive target for pharmacologic treatment (e.g., everolimus) and highlighting the importance of mutation profiling for individualized therapies (36). In our population, maybe because enriched in IBC (64% of the patients), with a rate of 40% in the entire population and of 31% in the TN subgroup, PIK3CA/mTOR pathway (altered in 22 patients, including 12 patients with IBC) appears the second most altered pathway, immediately after TP53 (52% and 61%, in the entire population and TN subgroup respectively).…”
Section: Secondary Objectivesmentioning
confidence: 99%
“…In ER-positive tumors with mutated PIK3CA, indicators of PI3K pathway activation (e.g., phosphorylated AKT and mTOR) were no different as compared to tumors without mutations [12], unless associated with PTEN loss, then both indicators were increased. In TNBC, both mutations were associated with overexpression of phosphorylated AKT [13]. Therefore, the functional effects of PI3K pathway alterations are probably subtype specific.…”
Section: Pik3ca Mutations In Breast Cancermentioning
confidence: 99%
“…PIK3CAm are most common in luminal estrogen receptor (ER)-positive tumors, especially in luminal A (49 vs 32 % in luminal B), approximately 25 % of HER2-positive tumors, and up to 23 % in triple negative breast cancers (TNBCs) [12][13][14]. PIK3CA is most frequently mutated at Bhot spots^in exons 9 and 20, corresponding to the helical (E542K and E545G) and kinase (H1047R) domains of the catalytic subunit p110a, respectively [15], accounting for up to 87.5 % of all mutations in PIK3CA [16].…”
Section: Pik3ca Mutations In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations